2010
DOI: 10.1523/jneurosci.5166-09.2010
|View full text |Cite
|
Sign up to set email alerts
|

Blood Oxygen Level-Dependent Signal Variability Is More than Just Noise

Abstract: Functional magnetic resonance imaging (fMRI) research often attributes blood oxygen level-dependent (BOLD) signal variance to measurement-related confounds. However, what is typically considered "noise" variance in data may be a vital feature of brain function. We examined fMRI signal variability during fixation baseline periods, and then compared SD-and mean-based spatial patterns and their relations with chronological age (20 -85 years). We found that not only was the SD-based pattern robust, it differed gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

53
461
3
2

Year Published

2013
2013
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 360 publications
(519 citation statements)
references
References 38 publications
53
461
3
2
Order By: Relevance
“…Notably, brain activity variability has been linked to task performance, development and disease and it has been suggested that signal variability is not "noise" but crucial for spontaneous or stimulated reorganizations of the brain (Garrett et al, 2010;McIntosh et al, 2008). Just as studies on brain signal variability provided novel insights into brain function, we believe that studies on brain connectivity variability will further our understanding of the brain's functional organization.…”
Section: Variability As a Signal In Its Own Rightmentioning
confidence: 92%
“…Notably, brain activity variability has been linked to task performance, development and disease and it has been suggested that signal variability is not "noise" but crucial for spontaneous or stimulated reorganizations of the brain (Garrett et al, 2010;McIntosh et al, 2008). Just as studies on brain signal variability provided novel insights into brain function, we believe that studies on brain connectivity variability will further our understanding of the brain's functional organization.…”
Section: Variability As a Signal In Its Own Rightmentioning
confidence: 92%
“…To note, BOLD-and CBF-ALFF were sensitive to physiological noises and were higher in the regions near large vessels and CSF. Although advanced preprocessing strategy including ICA noise removal Lowe, 2007, 2010) and additional regression of head motion, CSF and white matter time series (Garrett et al, 2010), could help to eliminate noise contaminations, the observations of residual noises suggests more work on denoising is needed such as physiological noise modeling using simultaneously recorded physiological pulsations and more robust indices for measurement of fluctuation amplitude.…”
Section: Group Average Maps Of Cbf-mean Bold-and Cbf-alff and Bold-mentioning
confidence: 99%
“…Although advanced preprocessing strategy including ICA noise components removal Lowe, 2007, 2010) and additional regression of head motion, CSF and white matter time series (Garrett et al, 2010), could help to eliminate noise contaminations, the observations of residual noises contamination suggested future work on denoising such as physiological noise modeling using simultaneously recorded physiological pulsations and more robust indices for measurement of fluctuation amplitude. Fractional ALFF (fALFF) was proposed to suppress these physiological noises by normalizing ALFF using a ratio between amplitude of low-frequency fluctuations and the amplitude of the overall frequency range.…”
Section: Test-retest Reliability Of Bold and Cbfmentioning
confidence: 99%
See 2 more Smart Citations